Effects of the TEDA4I Program on Preschool Children with Developmental Delays in Sub-district Health Promotion Hospitals - Wongseeda, Kasemsak; suktae, watchara; Pongnimitporn, Sarun (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Sakon Nakhon province has a higher number of children with suspected developmental delays than the national average. When the sub-district health promotion hospital identifies children with delayed development, they will be referred for developmental stimulation at the provincial hospitals only. The outcome evaluation of such services found that fewer children received services than the target because parents have to take their children for developmental stimulation multiple times, which affects their careers, and they experience difficulties in travel, children’s lack of cooperation, and unfamiliarity with personnel and location. The purpose of this study was to compare the average developmental scores of preschool children with developmental delays before and after receiving developmental stimulation with the TEDA4I program at the sub-district health promotion hospital. Methods This research was a quasi-experimental study with a single group measured before and after the experiment. The sample group was 30 preschool children with developmental delays who received services at the sub-district health promotion hospital. Purposive sampling was used to select the sample group. The tool used for the experiment was the TEDA4I program. Data analysis using the paired t-test statistics. Results The research findings indicated that preschool children with developmental delays after receiving developmental stimulation with the TEDA4I program showed a statistically significant increase in average developmental scores (p < .001). Conclusion and Recommendations The TEDA4I program helps preschool children with developmental delays improve their development. Therefore, Those involved in stimulating the development of preschool children with delayed development can use this stimulation tool to organize stimulation activities at sub-district health promotion hospitals and staff training should be supported.